The Fowl Twins Get What They Deserve : The Fowl Twins # 3 - Colfer, Eoin (Los Angeles ; New York : Disney Hyperion, 2021)
"Twins Myles and Beckett face off against Lord Teddy Bleedham-Drye, the Duke of Scilly, who has been plotting revenge against them since they humiliated him"--.
Ages 8-12.
Grades 4-6.
Keywords: Twins -- Fiction; Adventure and adventurers -- Fiction; Revenge -- Fiction; Cloning -- Fiction; Brothers -- Fiction; Fairies -- Fiction